Surgical management of subcutaneous cyst on the forelimb of a Royal Bengal Tiger (Bangladesh Veterinarian, 2014)
A 5 year-old female Royal Bengal Tiger (Panthera tigris tigris) was reported as having a cyst-like structure on the left forelimb, confirmed by physical examination under general anaesthesia with xylazine and ketamine and fine needle aspiration. Surgical intervention was done by making a small stab incision with drainage of bloody fluid. The inner cyst wall was disrupted and packed with gauze soaked in tincture of iodine. No suture was given. Ceftriaxone (Trizon vet®, ACME Laboratories limited, Dhaka, Bangladesh) 30mg/kg body weight was injected daily for seven days intramuscularly. Antiseptic dressing was done every alternate day for 7 days. After one week the cyst cavity and inflammation subsided and complete recovery was evident.DOI: http://dx.doi.org/10.3329/bvet.v30i2.18271 Bangl. vet. 2013. Vol. 30, No. 2, 78-80